Natural shading and productivity index of broiler chickens - Souza,Fernando A. (2015)
The appropriate use of natural resources in the design of broiler houses provides a reduction in farming operating costs and optimization of production conditions. Therefore, the natural shading around the broiler house can be an alternative for improving internal conditions of comfort. This study verified the efficiency of natural shading in the broiler productivity index (PI) in East-West oriented commercial housings. The PI of 32 commercial broiler houses in five flocks divided throughout a year was compared. The sheds had the same management, density and the same structural features, except from tree shading: on the North face; on the South face; on both faces and without shading. It was observed that broiler house in East-West direction with shading on the South face had higher productivity index compared to houses with shading only on the North face or on both sides, between autumn and spring. For the summer period, sheds without shading showed productivity indexes superior to others.